2001
DOI: 10.1292/jvms.63.461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrous Cycle on the Mouse Kidney Morphology.

Abstract: ABSTRACT. Although mice kidney morphology shows various sexual dimorphisms, the effect of the estrous cycle has not previously been discussed. In this study, we investigated the effects of the estrous cycle on kidney morphology, including renin-positive areas, of female DBA/2 mice. No effects were confirmed in most of the histometrical parameters, however, the percentage of the renal corpuscles in which cuboidal epithelium covered under 50% of the parietal layer was significantly higher during estrus compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A recent study demonstrated that development of vacuolar structures was stimulated by testosterone treatment but not affected by estradiol treatment [12]. In PAS-positive granules, although no effects of normal estrus have been identified [11], development of these granules is stimulated by estradiol treatment and inhibited by testosterone treatment [12]. These structures in male PCTs or female PSTs of DBA/2Cr mice were already confirmed as giant lysozomes by the electron microscopic studies [14,17].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study demonstrated that development of vacuolar structures was stimulated by testosterone treatment but not affected by estradiol treatment [12]. In PAS-positive granules, although no effects of normal estrus have been identified [11], development of these granules is stimulated by estradiol treatment and inhibited by testosterone treatment [12]. These structures in male PCTs or female PSTs of DBA/2Cr mice were already confirmed as giant lysozomes by the electron microscopic studies [14,17].…”
Section: Discussionmentioning
confidence: 95%
“…Vacuolar structures were prominent in PCTs of males but not females [12][13][14]. Variously sized PAS-positive granules were prominent in PSTs of females but not males [11][12][13][15][16][17][18]. Although these studies demonstrated that the gender differences were induced by testosterone or estradiol [12,19], the developmental process responsible for these gender differences in mouse kidney morphology has not been investigated previously.…”
mentioning
confidence: 99%
“…After the final wash, slides were mounted in Slowfade Light mounting medium (Molecular Probes) and examined using fluorescent microscopy. Pancreata for histological studies were fixed overnight in Bouin's fixative (20), paraffin-embedded, sectioned, and stained with hematoxylin͞eosin according to standard protocol.…”
Section: Generation Of the Rip-fas Cg Dna Construct And Evaluation Ofmentioning
confidence: 99%
“…In addition, livers, lungs, adrenal glands, submandibular glands and testes from the mice were prepared in a similar manner for immunohistochemistry to investigate extra-renal renin expression. The number of renin-positive areas was quantified as previously described [9,12], and analyzed using one-way analysis of variance (Bonferroni/Donn test).…”
mentioning
confidence: 99%